Serial evaluation of resting and exercising overground endoscopic examination results in young Thoroughbreds with no treatment intervention. (25th August 2018) - McGivney, C. L.; Sweeney, J.; Gough, K. F.; Hill, E. W.; Katz, L. M.
Summary: Background: We hypothesised that grade/appearance for upper respiratory tract (URT) disorders identified at the first overground endoscopy (OGE) examination would vary at subsequent examinations. Objectives: To compare OGE examinations from horses evaluated on at least two occasions under similar exercise conditions without treatment intervention. Study design: Retrospective cohort. Methods: Pre‐exercise and exercising OGE recordings from Thoroughbred horses undergoing multiple examinations under similar exercise conditions were reviewed, with the first two recordings for each horse statistically evaluated. Paired Wilcoxon signed‐rank tests were used to assess differences in exercise and physiological parameters between examinations. Z‐tests were used to assess the proportion of changes in URT disorder grade/appearance between examinations. A McNemar's test was used to compare the proportion of horses with each disorder at each examination. Test–retest reliability across examinations was assessed using Spearman's ρ, and ordered logistic regression used to explore temporal effects on repeatability. Lattice plots were constructed to view variability in disorders over time. Results: Seventy‐eight horses (median age 2.4 years) with 195 resting endoscopic examinations including 72/78 horses with 179 pre‐exercise and exercising OGE examinations were evaluated. Median time between examinations was 226.5 days with no differences between exercise and physiological parameters. Grades significantly varied between examinations for all disorders, and in particular for palatal instability (PI) and epiglottic grade at rest. A temporal link between examination interval and disorder grade change was identified for PI and resting arytenoid asymmetry. Main limitations: OGE re‐examinations within a shorter, more consistent time‐frame would allow determination of intrahorse variability. The sample size was inadequate to conclusively establish temporal links between disorders and time between examinations. Conclusions: Variability for most URT abnormalities identified with OGE should be considered when making therapeutic decisions based on a single examination and may partially explain development of additional URT conditions after surgical intervention. The Summary is available in Portuguese ‐ see Supporting Information